2000
DOI: 10.1108/07378830010333464
|View full text |Cite
|
Sign up to set email alerts
|

Empowering users with a new online catalog

Abstract: In June 1998 Oakland University's library migrated to a new online catalog. In order to determine user acceptance of the new OPAC, students receiving library instruction were asked to complete an open-ended questionnaire eliciting comments on their likes, dislikes and online catalog preference. From the data collected, a second questionnaire was designed and distributed that focused on specific features of the new catalog identified in the first survey. Results indicated that users overwhelmingly preferred the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 5 publications
1
4
0
1
Order By: Relevance
“…This is interesting because author or title search is more specific and requires a user to know exact author information or the exact first few words of a title before a search can be successfully executed. The finding suggests that certain groups of users knew exactly what they were looking out for and this, to a certain extent, is consistent with Lombardo and Condic's (2000) work which found that most OPAC users could identify whether they required an author or title search, but could not determine when to use subject search.…”
Section: Search Options Usedsupporting
confidence: 81%
See 1 more Smart Citation
“…This is interesting because author or title search is more specific and requires a user to know exact author information or the exact first few words of a title before a search can be successfully executed. The finding suggests that certain groups of users knew exactly what they were looking out for and this, to a certain extent, is consistent with Lombardo and Condic's (2000) work which found that most OPAC users could identify whether they required an author or title search, but could not determine when to use subject search.…”
Section: Search Options Usedsupporting
confidence: 81%
“…Nevertheless, users have been known to encounter difficulties in constructing effective search strategies using these features. For example, Lombardo and Condic (2000) conducted a survey on the new release of the OPAC system at Oakland University and discovered that many of its users were unable to take advantage of more sophisticated search techniques because the features were not intuitive. A separate study of the University of Colorado OPAC also showed that only 8.7% of all queries used advanced search features (Jansen & Pooch, 2000).…”
Section: Query Patternsmentioning
confidence: 99%
“…Others were looking for answers to questions, such as what the users believe they want and what they really need (Wallace, 1993; Novotny, 2004). There have been also studies of users' attitudes and behaviour before and after the implementation of an online catalogue in their library (Martinez‐Arellano, 1996; Dentinger, 1998; Lombardo and Condic, 2000). Furthermore, there were comparative studies of user behaviour over an OPAC and a card catalogue (Sridhar, 2004).…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Transaction logs, as a method of collecting data, is widely used in libraries (Burton and Hawkins, 1993; Wallace, 1993; Peters, 1996; McGlamery, 1997; Park, 1997; Martinez‐Arellano, 1996; Blecic et al , 1998, 1999; Dentinger, 1998; MacEwan, 1999; Banks, 2000; Lombardo and Condic, 2000; Novotny, 2004; Sridhar, 2004; Villen‐Rueda et al , 2007; Wolfram, 2008) because of its advantage of providing unbiased information about patron's behaviour when searching the OPAC. Patrons are not influenced by the researcher's presence and also their anonymity is protected, as patron identification is not required for the use of OPACs.…”
Section: Methodsmentioning
confidence: 99%